Fatores que influenciam na motivação dos servidores públicos: Hospital de Emergência Dr. Daniel Houly, Arapiraca/AL - Santos, Joseano Lira (2019)
The central objective of this study is to relate the organizational factors that interfere in the satisfaction and motivation of the public servants of the Dr. Daniel Houly Emergency Hospital (HEDH), located in Arapiraca/Alagoas. In this sense, relevant aspects were approached for a better understanding of what factors influence the motivation and satisfaction of the servers, and how these factors impact on the achievement of institutional goals, on the quality of service provision to users, as well as on the respective activities in the work environment. The research is an exploratory and descriptive study, with a qualitative approach, whose population is composed of the employees of the above-mentioned hospital, and the sample of 198 (one hundred and ninety-eight) servants of primary and secondary education levels, sectors of the respective hospital. The data collection technique was performed through a questionnaire containing thirty (30) questions - related to the motivogram developed by Maslow (1970), whose questionnaire was already validated and endorsed in other researches, which resulted in the identification of the motivational factors of the respective participating employees of the sample - distributed among the servers participating in the study. The data were tabulated and generated tables and graphs in Microsoft Excel, being analyzed and based mainly on Abrahm Maslow's hierarchy of human needs theory, as well as other motivational theories such as the "Two Factors of Herzberg" and "X and And of McGregor. " After analyzing the data collected, it was possible to identify and quantify the motivation variables - performance, autonomy, hierarchy/subordination, responsibility, promotion and productivity, respectively, elements of satisfaction considered relevant for professional and personal achievement of the group studied. tivational factors that contribute to an efficient and effective work environment, imparting importance and meaning to the server, whose results appear in the motivation for the work, that is, in the most relevant factors that are: "autonomy and responsibility at work, importance and meaning of the work for the server and like what it does "and the least contributing factor, but not least is" career advancement opportunity "; and the hygienic factors "physical environment and materials / tools for performing the work in HEDH appropriate for the accomplishment of the tasks, remuneration and difference of treatment between the servants" are the ones that are generating the most work dissatisfaction, whereas the factors "a good relationship with colleagues, stability and competence of the immediate bosses "are the ones that most influence positively avoiding the dissatisfaction of the servants. Therefore, these basic human needs or basic factors are the most valued and motivational satisfaction generators, identified by the HEDH/AL servers.